AB0410 The interplay between C3 and C4 and disease activity in patients affected by rheumatoid arthritis during treatment with ANTI-IL6 receptor. (15th June 2017) - Conigliaro, P; Triggianese, P; Chimenti, MS; Duca, I; Kroegler, B; Perricone, R
Abstract : Background: The complement system (CS) is involved in the pathogenesis of rheumatoid arthritis (RA). Evidence reported that high C3 levels C3 in RA patients might reflect a pro-inflammatory status and represent a negative prognostic factor for TNF-inhibitors therapy. Objectives: We evaluated CS in a cohort of RA patients treated with tocilizumab (TCZ) to explore whether there was any correlation between CS and both disease activity and response to therapy. Methods: Consecutive outpatients affected by RA who started TCZ treatment i.v. at the Rheumatology Unit of "Policlinico Tor Vergata" in Rome (Italy) were enrolled (n=25) (Table I). We included 25 healthy subjects as controls. Disease activity was assessed by using DAS28 ESR-based while clinical response to therapy by EULAR response criteria. Peripheral blood samples were obtained from all patients at the time of each infusion. Laboratory assessment included ESR, CRP, RF, ACPA, C3, C4, CH50 assay. Clinical and laboratory data were registered at baseline (T0), after 1 (T1), 3 (T3), 6 (T6), 9 (T9), and 12 (T12) months from the beginning of the TCZ treatment. Results: At baseline, both C3 and C4 were significantly higher in RA than in controls (Table 1 ). No difference in C3 and C4 resulted between ACPA positive and ACPA negative patients during the follow up. ESR, CRP and DAS28 levels were significanlty reduced at T1, T3, T6, T9, and T12 with the respect to T0 (Figure 1A-C). C3 levels were significantly reduced at T3, T6, and T9 with the respect to T0 while C4 levels were significantly reduced at T3, T6, T9, and T12 with the respect to T0 (Figure 1D-E). Positive correlations resulted between DAS28 and both C3 and C4 at T1 and T3 (Figure 1F-I). C3 and C4 were directly related with ESR at T1 (C3: P 0.002; C4: P 0.005), T3 (C3: P 0.04; C4: P 0.03), and T6 (C3: P<0.0001; C4: P 0.002) and with CRP at T1 (C3: P 0.03; C4: P 0.01) and T6 (C3: P<0.0001; C4: P 0.03). When stratifying patients in accordance with the EULAR response to therapy, C3 decreased significantly in responders than in no-responders at T1; moreover, responders showed lower levels of both C3 and C4 at T1 and T3 with the respect to T0 (Figure 1L-O). Conclusions: In RA patients, treatment with TCZ is able to reduce C3 and C4 levels in an early and substained way. The disease activity is directly related with the reduction of C3 and C4 serum levels. RA patients with a good/moderate clinical response show significantly lower C3 and C4 levels than no-responder patients. Our preliminary data suggest that C3 and C4 can be a reliable marker of both the disease activity and the response to therapy in RA patients treated with TCZ. Disclosure of Interest: None declared